Raised Intraocular Pressure Following Phacoemulsification; A Comparative Study with Two Different Viscoelastic: Raised Intraocular Pressure Following Phacoemulsification - Jamal Khan, Ahmed; Rehman, Maqbool-ur; Ashraf , Awais; Sajid Khan, Muhammad; Ullah, Ubaid; Malik, Aeeza (Pakistan Journal of Health Sciences, 2022)
The new modalities in surgical phacoemulsification techniques are intended to restore the visual acuity and have minimized postoperative astigmatism. Objective: To evaluate the difference in the raised intraocular pressure after phacoemulsification and insertion of an intraocular lens using 2% hydroxymethyl cellulose and 1% sodium hyaluronate as viscoelastic. Methods: This group comparative study was performed in the Department of Ophthalmology, Khyber Teaching Hospital, Peshawar for six months. A thorough slit lamp examination was executed to confirm intraocular inflammation or proof of prior intraocular surgery. For glaucoma, Gonioscopy was performed along with proper fundus examination. Patients in Group 1 received 2% Hydroxymethyl Cellulose while in Group 2 patients received 1% Sodium Hyaluronate as viscoelastic. No pressure lowering drug was used and mean intraocular pressure was calculated using Goldman Applanation Tonometer. Intraocular pressure was measured preoperatively and then after 6, 12 and 24 hours and then after one week of surgery. Results: In Group 1, mean age was 65 ± 8.5 and mean Pre Op IOP was 13.1 ± 2.1. Mean Postop IOPs were 13.8, 14.2, 15.1 and 17.5 at 6, 12, and 24 hours and after 1 week respectively. In Group 2, mean age was 62.7 ± 8.3 and mean Preop IOP was 13.2 ± 2.3. Mean Postop IOPs were 13.5, 13.9, 15.1 and 15.9 at 6, 12, and 24 hours and after 1 week respectively. Conclusions: Mean intraocular pressure rise was significantly greater at one week after phacoemulsification and insertion of an intraocular lens using 2% hydroxymethyl cellulose as viscoelastic.